Enhancing efficiency in capacitive power transfer: exploring gap distance and load robustness - Yusop, Yusmarnita; Cheok, Yan Qi; Saat, Shakir; Husin, Huzaimah (International Journal of Electrical and Computer Engineering (IJECE), 2024)
In this paper, the capacitive power transfer (CPT) technology is used as an alternative to inductive power transfer (IPT). CPT relies on electric fields that are not sensitive to the presence of any metals, utilizes metal electrodes for power transfer, and is less bulky compared to IPT. The proposed CPT system utilizes a Class-E resonant inverter with a double-sided inductor-capacitor (LC) matching circuit which operates at an optimum load, with a duty cycle, D=0.5 to gain an output power, W and efficiency, η=84.6%. The proposed CPT system enhances the system’s efficiency as compared to the past research while preserving the zero-voltage switching (ZVS) condition within a wider load range from 50 Ω to 1,316 Ω. This paper also shows that the proposed CPT system is less sensitive to load and coupling variations. Finally, the rate of power dissipated at varied load resistances, has been derived successfully to determine the sensitivity level of the proposed CPT systems toward load variations. These equations are then validated by plotting the efficiency graphs based on load and coupling variations.